DESKRIPSI STANDAR DAN GAYA HIDUP KEKRISTENAN SEBAGAI ARAH PENDIDIKAN AGAMA KRISTEN - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati Yeniretnowati (Sekolah Tinggi Teologi Duta Panisal, 2022)
Today many people profess to be Christians but their lives are still far from the andard of living and lifestyle modeled by Jesus. It is even more ironic that a similarm life as demonstrated and exemplified by Jesus is considered impossible to do while on this earth and not for Christians to practice today. This study uses a literature review method, namely by analyzing the concept of what is the standard of living and lifestyle that Christ modeled and wore as a framework for the concept of Christian standards and lifestyle as a direction for the development and Christian education. The results of this study show the concepts and implications for the direction of Christian Religious Education in producing and shaping Christians who imitate Jesus.